An integrated low-temperature high-pressure hydrogen storage container for a drone and a manufacturing method thereof
Patent Information
- Application Number
- CN202611097535.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-23
AI Technical Summary
[0004]本申请提供一种无人机用一体化低温高压的储氢容器及其制造方法,其解决了现有低温高压储氢容器难以兼顾无人机应用所需的轻量化、高质量储氢密度、高压承载能力、低温绝热性能和抗冲击安全性的技术问题
[0018] The technical solution provided by one or more embodiments of this application forms an integrated sandwich structure with airtightness, pressure bearing, heat insulation, and impact resistance by sequentially arranging a metal liner structure, a composite pressure-bearing layer, a non-vacuum closed-cell foam layer, and a composite shell from the inside out. The metal liner structure forms the hydrogen storage cavity and blocks hydrogen permeation; the composite pressure-bearing layer bears the main pressure loads under low-temperature and high-pressure conditions, including axial and circumferential stresses, and together they ensure the structural integrity and airtightness of the hydrogen storage cavity under extreme conditions. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, effectively blocks heat transfer and achieves lightweighting by utilizing its low thermal conductivity and low density characteristics. Furthermore, the non-vacuum closed-cell foam layer absorbs impact energy through pore wall buckling, plateau crushing, and shear deformation mechanisms, which, combined with the load diffusion effect of the outer composite shell, provides effective impact protection for the internal pressure-bearing layer and the metal liner. This integrated structure enables the hydrogen storage container to meet multiple functional requirements, including low-temperature insulation, high-pressure bearing, lightweighting, and impact resistance.
Smart Images

Figure CN122590200B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of hydrogen storage container technology, and in particular to an integrated cryogenic high-pressure hydrogen storage container for unmanned aerial vehicles and its manufacturing method. Background Technology
[0002] Existing hydrogen storage technologies for hydrogen fuel cell drones have the following shortcomings: 35 / 70MPa high-pressure gaseous hydrogen storage technology is mature but has low hydrogen storage density, and increasing the gas cylinder capacity will reduce the payload and shorten the flight range; traditional low-temperature hydrogen storage containers rely on bulky vacuum multilayer insulation structures, which pose a risk of vacuum loss under drone vibration, drop, or local impact conditions; existing research focuses more on thermal insulation performance and does not take full advantage of the dual characteristics of closed-cell foam in "thermal insulation + crushing energy absorption", and there are no parameter design specifications suitable for drone scenarios. Other complex hydrogen storage solutions are difficult to meet the lightweight requirements of drones.
[0003] Therefore, how to solve the problem that existing low-temperature high-pressure hydrogen storage containers cannot simultaneously meet the requirements of drone applications, such as lightweight design, high-quality hydrogen storage density, high-pressure load-bearing capacity, low-temperature insulation performance, and impact resistance, has become an urgent technical issue to be addressed. Summary of the Invention
[0004] This application provides an integrated cryogenic high-pressure hydrogen storage container for unmanned aerial vehicles (UAVs) and its manufacturing method, which solves the technical problems of existing cryogenic high-pressure hydrogen storage containers that are difficult to simultaneously meet the requirements of UAV applications, such as lightweight, high-quality hydrogen storage density, high-pressure bearing capacity, cryogenic insulation performance and impact resistance.
[0005] To achieve the above objectives, the main technical solutions adopted in this application include: In a first aspect, embodiments of this application provide an integrated cryogenic high-pressure hydrogen storage container for unmanned aerial vehicles (UAVs). The hydrogen storage container is applied to a UAV hydrogen fuel cell system, and comprises, from the inside out: A metal liner structure is used to form a hydrogen storage cavity; A composite material bearing layer covers the outside of the metal liner structure; A non-vacuum closed-cell foam layer fills and covers the outside of the composite material pressure-bearing layer; A composite material shell covers the outside of the non-vacuum closed-cell foam layer; The composite material pressure-bearing layer, the non-vacuum closed-cell foam layer, and the composite material shell constitute an integrated sandwich structure. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, is configured to provide both thermal insulation and impact resistance.
[0006] In one embodiment, the non-vacuum closed-cell foam layer fills the interlayer space between the composite pressure-bearing layer and the composite shell; wherein, apart from the closed-cell cavity of the non-vacuum closed-cell foam layer itself, there is no independent sealed cavity in the interlayer space for forming vacuum insulation, and the difference between the gas pressure in the interlayer space and the external ambient gas pressure of the hydrogen storage container is ≤5kPa.
[0007] In one embodiment, the material parameters of the non-vacuum closed-cell foam layer meet the following requirements: Closed-cell ratio ≥90%; Density is 20-80 kg / m³ 3 ; Under the condition of temperature 293-303K, the apparent thermal conductivity is ≤0.050W / (m•K); Under conditions of 40-110K, the apparent thermal conductivity is ≤0.020W / (m•K); The crushing stress on the platform is 0.2-3 MPa; Densification strain ≥ 0.4.
[0008] In one embodiment, the thickness of the non-vacuum closed-cell foam layer is 5-80 mm, and the ratio of the thickness of the non-vacuum closed-cell foam layer to the outer radius of the hydrogen storage container is 0.03-0.50.
[0009] In one embodiment, the outer surface of the composite material pressure-bearing layer is provided with an interface reinforcement structure, and the non-vacuum closed-cell foam layer is filled into the interface reinforcement structure by an in-situ foaming process, and forms a mechanical interlocking with the composite material pressure-bearing layer after curing.
[0010] In one embodiment, the interface enhancement structure includes at least one of the following: surface roughening structure, microporous structure, shallow groove structure, mesh texture, local protrusions, fibrous felt layer, or porous transition layer; wherein... When the interface enhancement structure is a surface roughening structure, the surface roughness of the surface roughening structure is 5-80 μm; When the interface enhancement structure is a shallow groove structure, the groove depth is 0.05-0.5mm, the groove width is 0.1-1.5mm, and the groove spacing is 0.5-5mm. When the interface enhancement structure is a microporous structure, the pore diameter of the microporous structure is 20-500 μm and the pore depth is 0.02-0.5 mm.
[0011] In one embodiment, the interfacial shear strength between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥0.3 MPa.
[0012] In one embodiment, after the hydrogen storage container undergoes ≥100 thermal cycles at a temperature between 77-300K, the interfacial shear strength retention rate between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥75%, and / or, the interfacial shear strength retention rate between the non-vacuum closed-cell foam layer and the composite shell is ≥75%.
[0013] In one embodiment, the composite material shell has a thickness of 0.3-3 mm and is configured to diffuse the impact load area to at least twice the impact contact area when subjected to a point impact.
[0014] In one embodiment, the performance indicators of the hydrogen storage container include: The design temperature is 40-110K; The design pressure is 10-70 MPa; Mass hydrogen storage density ≥10%; The non-venting holding time before reaching the safe relief pressure is ≥12 hours; Under ambient temperature ≤333K, the apparent heat leakage flux density is ≤100W / m³. 2 ; The theoretical energy absorption of the non-vacuum closed-cell foam layer is ≥200J.
[0015] In one embodiment, the metal liner structure is made of a low-temperature hydrogen-compatible metal material, which is selected from at least one of 6061 aluminum alloy, 6063 aluminum alloy, 5083 aluminum alloy, 304L stainless steel, 316L stainless steel or TC4 titanium alloy. The composite pressure-bearing layer is made of carbon fiber reinforced low-temperature resistant resin matrix composite material, which is formed by mixing carbon fiber and resin material. The carbon fiber is selected from at least one of T700, T700S, T800, T800H, T1000, T1000G or T1100G; the resin material is selected from at least one of low-temperature resistant epoxy resin, modified epoxy resin, cyanate ester resin or bismaleimide resin. The non-vacuum closed-cell foam layer is selected from at least one of polyurethane foam, polyisocyanurate foam, polymethacrylamide foam, phenolic foam, polyvinyl chloride foam, polyetherimide foam, aerogel-reinforced foam, or hollow microsphere-reinforced foam. The composite material shell is made of fiber-reinforced resin-based composite material, which is selected from at least one of carbon fiber-reinforced epoxy resin-based composite material, glass fiber-reinforced epoxy resin-based composite material, and aramid fiber-reinforced resin-based composite material.
[0016] Secondly, embodiments of this application provide a method for manufacturing the aforementioned hydrogen storage container, the method comprising: Provide a metal lining structure; Fibers are wound around the outer surface of the metal liner structure to form a composite material bearing layer, and then a first curing treatment is performed. A non-vacuum closed-cell foam layer is formed on the outside of the cured composite material pressure-bearing layer; Fibers are wound around the outer surface of the non-vacuum closed-cell foam layer to form a composite material shell, and a second curing process is performed to make the composite material shell, the non-vacuum closed-cell foam layer and the composite material pressure-bearing layer form an integrated sandwich structure.
[0017] In one embodiment, both the first curing process and the second curing process employ multi-stage temperature-increasing curing; the multi-stage temperature-increasing curing includes: First stage: Incubate at 353-363K for 0.5-1 hour; Second stage: Heat to 383-393K and hold for 2-3 hours; Third stage: Heat to 403-413K and hold for 2-3 hours; The heating rate of both the first curing process and the second curing process is controlled at 274-276 K / min between each stage.
[0018] The technical solution provided by one or more embodiments of this application forms an integrated sandwich structure with airtightness, pressure bearing, heat insulation, and impact resistance by sequentially arranging a metal liner structure, a composite pressure-bearing layer, a non-vacuum closed-cell foam layer, and a composite shell from the inside out. The metal liner structure forms the hydrogen storage cavity and blocks hydrogen permeation; the composite pressure-bearing layer bears the main pressure loads under low-temperature and high-pressure conditions, including axial and circumferential stresses, and together they ensure the structural integrity and airtightness of the hydrogen storage cavity under extreme conditions. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, effectively blocks heat transfer and achieves lightweighting by utilizing its low thermal conductivity and low density characteristics. Furthermore, the non-vacuum closed-cell foam layer absorbs impact energy through pore wall buckling, plateau crushing, and shear deformation mechanisms, which, combined with the load diffusion effect of the outer composite shell, provides effective impact protection for the internal pressure-bearing layer and the metal liner. This integrated structure enables the hydrogen storage container to meet multiple functional requirements, including low-temperature insulation, high-pressure bearing, lightweighting, and impact resistance. Attached Figure Description
[0019] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 A flowchart illustrating a method for manufacturing a hydrogen storage container as provided in an embodiment of this application; Figure 2 Example 1 provides a schematic diagram of a cryogenic high-pressure hydrogen storage container applied to a hydrogen fuel cell system for unmanned aerial vehicles.
[0020] Explanation of reference numerals in the attached figures 1-Metal inner lining structure, 2-Composite pressure-bearing layer, 3-Non-vacuum closed-cell foam layer, 4-Composite outer shell. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0022] Hydrogen fuel cell drones have been demonstrated and applied in various scenarios such as power line inspection, emergency communication, logistics and transportation, surveying and mapping, marine monitoring and high-altitude operations due to their core advantages of long endurance, high refueling efficiency, low noise and zero carbon emissions. However, the quality, volume and safety performance of the hydrogen storage system directly affect the maximum takeoff weight, payload space and flight endurance of the drone, which are the core bottlenecks restricting the performance upgrade of hydrogen fuel cell drones.
[0023] Currently, hydrogen storage solutions for hydrogen-powered drones in the industrial sector mainly rely on high-pressure gaseous hydrogen storage. The most widely used method is the 35MPa Type III composite material wound gas cylinder. This type of solution has a high degree of technological maturity and can meet the hydrogen supply and safety requirements in conventional scenarios. However, at room temperature, its volumetric hydrogen storage density and mass hydrogen storage density are difficult to further improve. If the total amount of hydrogen stored is increased simply by increasing the volume or number of gas cylinders, it will inevitably lead to a significant increase in the total mass and space occupied by the hydrogen storage system. This will compress the drone's effective payload, limit the airframe layout, increase the difficulty of center of gravity control, and ultimately limit the improvement of the drone's endurance performance. It cannot meet the core requirements of drones for lightweight design and high hydrogen storage density.
[0024] To overcome the energy density bottleneck of high-pressure gaseous hydrogen storage, cryogenic liquid hydrogen or cryogenic high-pressure hydrogen storage has become an important direction for technological exploration. Traditional cryogenic hydrogen storage containers typically employ a high-vacuum multi-layer insulation structure to reduce heat leakage from the environment to the storage cavity. This type of structure is mostly designed for long-term ground storage, stationary liquid hydrogen storage tanks, or large cryogenic storage and transportation equipment. It usually requires components such as a vacuum interlayer, multiple layers of insulation materials, vacuum interfaces, vacuum valves, and vacuum monitoring devices between the pressurized inner container and the outer shell, thus increasing the container's structural weight, manufacturing complexity, and maintenance difficulty. More importantly, for drone applications, hydrogen storage containers may face complex conditions such as vibration, drops, and localized point loads during transportation, takeoff, landing, emergency landing, or mission execution. When the vacuum interlayer experiences sealing damage or a decrease in vacuum, the container's insulation performance will degrade. Once the vacuum layer is severely damaged, leading to vacuum loss, the insulation performance will rapidly decline, directly resulting in increased internal heat leakage, faster pressure rise, and a higher frequency of safe venting, significantly increasing safety risks.
[0025] Currently, some industry research has explored and attempted to optimize cryogenic hydrogen storage solutions for drones. Some studies use polyurethane foam as an insulation layer for liquid hydrogen containers, while others attempt to integrate hydrogen storage components with the airframe structure's floats, support rods, and skin. However, these explorations still have several shortcomings: First, in these solutions, polyurethane foam only serves as cryogenic insulation and is not explicitly designed as the core material for the crushing and energy-absorbing interlayer on the outside of the composite material's pressure-bearing layer. Furthermore, the crushing platform stress, densification strain, and thickness parameters of the foam are not considered in conjunction with the shell's constraint effect to assess its impact resistance. Second, the core design goal of the aircraft's hydrogen storage structure is to optimize the airframe layout, utilize buoyancy, or save space. Targeted optimization has not been conducted for the three core requirements of independent cryogenic high-pressure hydrogen storage containers for drones: "high hydrogen storage density, long non-venting hold time, and drop impact safety." Third, even when traditional cryogenic containers are equipped with both insulation layers and external buffers... The existing low-temperature hydrogen storage solutions are merely simple superpositions of different functions, failing to fully utilize the material properties of closed-cell foam, which simultaneously possesses low thermal conductivity and crushing energy absorption, making it difficult to achieve a balance between thermal insulation performance, impact resistance, and lightweight design. Fourth, there is currently a lack of design guidelines for non-vacuum foam thermal insulation and energy absorption interlayers that are suitable for the "short-term mission, continuous hydrogen supply" usage window of UAVs. In other words, there is no systematic design specification that simultaneously defines foam density, closed-cell rate, thermal conductivity, crushing platform stress, densification strain, foam thickness, shell thickness, mass hydrogen storage density, non-venting holding time, and foam layer buffering energy absorption indicators. Existing low-temperature hydrogen storage solutions are difficult to meet the comprehensive usage requirements of UAVs. Fifth, some liquid hydrogen non-destructive storage, vapor recovery, or refrigeration recovery solutions require additional complex components such as compound hydrogen storage containers, reactors, waste heat recovery devices, or refrigeration cold heads, which are difficult to match the core requirements of UAVs for lightweight structure and simplified gas path.
[0026] In summary, how to provide a low-temperature, high-pressure hydrogen storage container that balances the requirements of drone applications, such as lightweight design, high-quality hydrogen storage density, high-pressure load-bearing capacity, low-temperature insulation performance, and impact resistance, has become a pressing technical problem to be solved in the design of hydrogen fuel cell drone hydrogen storage systems.
[0027] According to an embodiment of this application, an integrated cryogenic high-pressure hydrogen storage container for unmanned aerial vehicles (UAVs) is provided. The hydrogen storage container is applied to a hydrogen fuel cell system of the UAV, and the hydrogen storage container comprises, from the inside to the outside: A metal liner structure is used to form a hydrogen storage cavity; Composite material bearing layer, covering the outside of the metal liner structure; A non-vacuum closed-cell foam layer fills and covers the outside of the composite material pressure-bearing layer; A composite material shell is used to cover the outside of a non-vacuum closed-cell foam layer; The composite material pressure-bearing layer, the non-vacuum closed-cell foam layer, and the composite material shell constitute an integrated sandwich structure. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, is configured to provide both thermal insulation and impact resistance.
[0028] Specifically, the metal liner structure forms the hydrogen storage cavity and prevents hydrogen permeation, while also serving as the mandrel for the composite pressure-bearing layer to be wound. Secondly, the composite pressure-bearing layer covers the outside of the metal liner structure and is used to bear the main pressure loads under low-temperature and high-pressure conditions, including axial and circumferential stresses.
[0029] Based on this, a non-vacuum closed-cell foam layer is filled and wrapped around the outside of the composite pressure-bearing layer. Unlike traditional cryogenic hydrogen storage containers that rely on vacuum interlayers for insulation, this application uses a non-vacuum closed-cell foam layer as the insulation medium, allowing the hydrogen storage container to maintain its cryogenic state without the need for a separate vacuum insulation cavity, effectively reducing the manufacturing complexity and overall weight of the hydrogen storage container. Finally, a composite material shell is wrapped around the outside of the non-vacuum closed-cell foam layer, serving as the external protective layer of the hydrogen storage container.
[0030] Furthermore, the composite pressure-bearing layer, the non-vacuum closed-cell foam layer, and the composite shell together constitute an integrated sandwich structure. In this integrated sandwich structure, the non-vacuum closed-cell foam layer, as the core material, is configured to simultaneously provide thermal insulation and impact resistance. Specifically, under normal or low-temperature conditions, the non-vacuum closed-cell foam layer utilizes the low thermal conductivity and low density characteristics of closed-cell foam materials to reduce heat transfer from the environment to the hydrogen storage cavity and achieve weight reduction. When the hydrogen storage container is subjected to a drop or localized impact, the composite shell diffuses the localized impact load into a distributed load with a larger effective pressure-bearing area, and transfers it to the non-vacuum closed-cell foam layer, which absorbs a large amount of impact energy through pore wall buckling, plateau crushing, and shear deformation, thereby protecting the internal composite pressure-bearing layer and metal liner structure from damage.
[0031] Preferably, the metal lining structure is made of a low-temperature hydrogen-compatible metal material, which is selected from at least one of 6061 aluminum alloy, 6063 aluminum alloy, 5083 aluminum alloy, 304L stainless steel, 316L stainless steel or TC4 titanium alloy; preferably 6061 aluminum alloy.
[0032] Preferably, the performance indicators of the hydrogen storage container include: a design temperature of 40-110K; a design pressure of 10-70MPa; a hydrogen storage density of ≥10% by mass; a non-venting holding time of ≥12h before reaching the safe release pressure; and an apparent heat leakage flux density of ≤100W / m³ under ambient temperature ≤333K. 2 The theoretical energy absorption of a non-vacuum closed-cell foam layer is ≥200J.
[0033] This embodiment provides an integrated cryogenic high-pressure hydrogen storage container. By sequentially arranging a metal liner structure, a composite pressure-bearing layer, a non-vacuum closed-cell foam layer, and a composite outer shell from the inside out, an integrated sandwich structure is formed, possessing airtightness, pressure bearing, thermal insulation, and impact resistance. The metal liner structure forms the hydrogen storage cavity and blocks hydrogen permeation. The composite pressure-bearing layer bears the main pressure loads under cryogenic and high-pressure conditions, including axial and circumferential stresses. Together, they ensure the structural integrity and airtightness of the hydrogen storage cavity under extreme conditions. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, utilizes its low thermal conductivity and low density to effectively block heat transfer and achieve lightweighting. Furthermore, this non-vacuum closed-cell foam layer absorbs impact energy through pore wall buckling, plateau crushing, and shear deformation mechanisms. Combined with the load diffusion effect of the outer composite outer shell, it provides effective impact protection for the internal pressure-bearing layer and the metal liner. The integrated structure allows the hydrogen storage container to meet multiple functional requirements, including cryogenic insulation, high-pressure bearing, lightweighting, and impact resistance.
[0034] In a preferred embodiment, a non-vacuum closed-cell foam layer fills the interlayer space between the composite pressure-bearing layer and the composite shell; wherein, apart from the closed-cell cavity of the non-vacuum closed-cell foam layer itself, there is no independent sealed cavity in the interlayer space for forming vacuum insulation, and the difference between the gas pressure in the interlayer space and the external ambient gas pressure of the hydrogen storage container is ≤5kPa.
[0035] Specifically, a non-vacuum closed-cell foam layer serves as the core material, completely filling the annular or columnar sandwich space formed by the outer surface of the composite pressure-bearing layer and the inner surface of the composite shell. The non-vacuum closed-cell foam layer is tightly bonded to both the composite pressure-bearing layer and the composite shell, serving to support the shell, transfer loads, and provide auxiliary thermal insulation.
[0036] Non-vacuum closed-cell foam refers to foam materials with a large number of closed pores. Closed-cell means that the pore structure inside the foam is mainly surrounded by pore walls, and adjacent pores are basically not connected. Non-vacuum means that during the preparation and curing process, the non-vacuum closed-cell foam layer is not maintained in an insulating state by vacuuming, and its pores are filled with atmospheric pressure gas (such as air or foaming agent gas), rather than being in a vacuum state.
[0037] Preferably, the composite pressure-bearing layer is made of carbon fiber reinforced low-temperature resistant resin matrix composite material, with carbon fiber as the reinforcement and low-temperature resistant resin as the matrix material. The carbon fiber is selected from at least one of T700, T700S, T800, T800H, T1000, T1000G, or T1100G; the resin material is selected from at least one of low-temperature resistant epoxy resin, modified epoxy resin, cyanate ester resin, or bismaleimide resin. The non-vacuum closed-cell foam layer is selected from at least one of polyurethane foam, polyisocyanurate foam, polymethacrylimide foam, phenolic foam, polyvinyl chloride foam, polyetherimide foam, aerogel-reinforced foam, or hollow microsphere-reinforced foam; The composite material shell is made of fiber-reinforced resin-based composite material, which is selected from at least one of carbon fiber-reinforced epoxy resin-based composite material, glass fiber-reinforced epoxy resin-based composite material, and aramid fiber-reinforced resin-based composite material.
[0038] This embodiment defines the structure of the interlayer space between the composite pressure-bearing layer and the composite shell. Specifically, except for the closed-cell cavities of the non-vacuum closed-cell foam layer itself, there is no independent sealed cavity within the interlayer space for forming vacuum insulation. This means that the gap between the composite pressure-bearing layer and the composite shell is continuously filled by a non-vacuum closed-cell foam layer. Unlike existing vacuum multilayer insulation structures, this embodiment does not have a macroscopic cavity or gap formed by vacuuming to maintain the vacuum insulation state between the composite pressure-bearing layer and the composite shell, nor does it rely on vacuum interfaces, vacuum valves, or vacuum monitoring structures to achieve insulation. This design avoids the complex process of creating a high vacuum environment between the composite shell and the composite pressure-bearing layer, reducing the manufacturing complexity and added weight of the hydrogen storage container. Simultaneously, it reduces the risk of insulation performance degradation and accelerated internal pressure rise caused by a decrease in vacuum level after shell damage or seal failure in traditional vacuum insulation structures.
[0039] Furthermore, the difference between the macroscopic gas pressure within the confined interlayer space and the external ambient gas pressure of the hydrogen storage container should be ≤5 kPa. The macroscopic gas pressure within the interlayer space refers to the gas pressure outside the closed-cell cavities of the non-vacuum closed-cell foam layer, and the gas pressure within the minute interface gaps (if present) between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer and the composite shell. The external ambient gas pressure refers to the actual atmospheric pressure in the environment where the hydrogen storage container is located. Under conventional test conditions at sea level or near the ground, the external ambient gas pressure can typically be approximated as standard atmospheric pressure (approximately 101.325 kPa).
[0040] The pressure difference is ≤5 kPa, preferably ≤3 kPa, and more preferably ≤1 kPa. The macroscopic gas pressure in the interlayer space is essentially equivalent to the external ambient pressure. This indicates that the non-vacuum closed-cell foam layer is cured and formed under normal or near-normal pressure, and its internal pore pressure is basically in balance with the external ambient pressure.
[0041] If a high-vacuum cavity or a large negative-pressure cavity is formed between the composite pressure-bearing layer and the composite shell, the composite shell may be subjected to additional external pressure loads generated by the pressure difference between the external ambient pressure and the interlayer space, increasing the risk of local deformation, buckling, interface debonding, or pressure instability of the foam layer. By controlling the pressure difference to within 5 kPa, it is ensured that the composite shell mainly bears the uniform radial support force provided by the internal non-vacuum closed-cell foam layer, rather than the compressive load of the external atmospheric pressure, thereby guaranteeing the structural integrity and dimensional stability of the hydrogen storage container.
[0042] This embodiment continuously fills the interlayer space between the composite pressure-bearing layer and the composite shell with a non-vacuum closed-cell foam layer, and limits the absence of an independent sealed cavity outside the closed-cell cavity of the non-vacuum closed-cell foam layer itself to form vacuum insulation. This fundamentally eliminates the high-vacuum manufacturing process required for traditional vacuum multilayer insulation structures, significantly reducing the manufacturing complexity, additional structural weight, and production cost of the hydrogen storage container. At the same time, by controlling the difference between the macroscopic gas pressure in the interlayer space and the external ambient gas pressure within the range of ≤5kPa, the pressure of the foam cells inside the non-vacuum closed-cell foam layer is kept basically balanced with the external ambient pressure. This avoids the risk of buckling deformation or crushing of the composite shell caused by the pressure difference between the inside and outside due to the attempt to form a partial vacuum. It ensures that the shell mainly bears the uniform radial support force provided by the non-vacuum closed-cell foam layer rather than the compressive load of the external atmospheric pressure, thereby effectively protecting the structural integrity of the foam core material and the stress uniformity of the composite pressure-bearing layer. It also eliminates the hidden danger of a sharp decline in insulation performance due to vacuum failure caused by shell damage. Ultimately, it ensures the structural stability, dimensional accuracy, and long-term insulation reliability of the hydrogen storage container under normal or near-normal pressure environments.
[0043] In a preferred embodiment, the material parameters of the non-vacuum closed-cell foam layer meet the following requirements: closed-cell rate ≥ 90%; density 20-80 kg / m³. 3 Under conditions of 293-303K, the apparent thermal conductivity is ≤0.050W / (m•K); under conditions of 40-110K, the apparent thermal conductivity is ≤0.020W / (m•K); the crushing plateau stress is 0.2-3MPa; and the densification strain is ≥0.4.
[0044] Specifically, the closed-cell ratio refers to the percentage of the volume of closed pores in a non-vacuum closed-cell foam layer relative to the total volume of the foam cells. This embodiment requires a closed-cell ratio of ≥90%, preferably ≥95%. A high closed-cell ratio is beneficial for improving the low-temperature insulation performance and compression energy absorption stability of the non-vacuum closed-cell foam layer. In the hydrogen storage container structure of this embodiment, a high closed-cell ratio reduces the interconnected pores within the foam, suppressing gas convection heat transfer between pores, thereby reducing the apparent thermal conductivity of the non-vacuum closed-cell foam insulation and energy absorption layer. Simultaneously, the closed-cell structure, together with the pore walls, provides compression support during compression, enabling the foam layer to form a relatively stable plateau stress response during compression deformation. This provides uniform radial support for the composite material pressure-bearing layer, reducing the risk of local instability or premature collapse.
[0045] Density refers to the apparent density of a non-vacuum closed-cell foam layer, that is, the mass of foam material per unit volume. The density is typically limited to 20-80 kg / m³. 3 Within the range, preferably 30~60kg / m 3 More preferably 28~36kg / m 3 This density range is designed to achieve a good balance between lightweight design, cryogenic insulation performance, and compressive energy absorption capacity. If the density is below 20 kg / m³... 3 Non-vacuum closed-cell foam layers have a low pore wall skeleton content, which may result in insufficient compressive strength and crush plateau stress, making it difficult to provide stable support between the composite pressure-bearing layer and the composite shell, and also making it difficult to meet the energy absorption requirements under external impact loads; if the density is higher than 80 kg / m³, 3 Although the compressive strength and plateau stress of foam materials are usually improved, the structural mass of hydrogen storage containers will be increased. At the same time, a higher proportion of solid-phase skeleton may increase the solid-phase thermal conductivity contribution of foam materials, which will increase the apparent thermal conductivity of non-vacuum closed-cell foam insulation energy absorption layer, thus which is not conducive to low-temperature insulation performance.
[0046] In this embodiment, the apparent thermal conductivity of the non-vacuum closed-cell foam layer is limited under both ambient temperature characterization conditions and low-temperature service conditions to ensure that the foam layer has good thermal insulation performance during material selection, ambient temperature storage, transportation, and low-temperature high-pressure hydrogen storage service.
[0047] Characterization conditions at room temperature (293~303K): Within this temperature range (i.e., normal room temperature environment), the apparent thermal conductivity is ≤0.050W / (m·K), preferably ≤0.035W / (m·K), and more preferably ≤0.030W / (m·K). This index can be used to evaluate the basic thermal insulation capacity of foam materials under room temperature conditions, which is beneficial for reducing environmental heat transfer from hydrogen storage containers during room temperature storage, transportation, or preparation for refueling.
[0048] Cryogenic service conditions (40~110K): Within this temperature range (i.e., the service temperature of cryogenic high-pressure hydrogen), the apparent thermal conductivity is ≤0.020W / (m·K), preferably ≤0.015W / (m·K), and more preferably ≤0.011W / (m·K). This parameter characterizes the insulation capacity of the foam layer under cryogenic high-pressure hydrogen storage conditions. By limiting the cryogenic apparent thermal conductivity, heat leakage from the environment to the hydrogen storage cavity can be reduced, delaying the temperature rise and pressure increase of hydrogen within the storage cavity, thereby improving the non-venting holding time of the hydrogen storage container and the stability of cryogenic hydrogen storage.
[0049] The crushing plateau stress refers to the average stress value of a non-vacuum closed-cell foam layer during the plateau compression stage from initial yielding to densification on a uniaxial compressive stress-strain curve. During this stage, the closed-cell walls within the foam material buckle, fold, undergo plastic yielding, or brittle fracture, allowing the foam layer to continuously compress and absorb external impact energy under a relatively stable stress level. In this embodiment, it is limited to 0.2~3 MPa, preferably 0.5~1.5 MPa. This parameter is used to limit the load-bearing and energy absorption capacity of the foam layer under external impact loads. When a hydrogen storage container is subjected to complex external loads, limiting the crushing plateau stress within the above range can prevent premature crushing of the foam layer due to excessively low plateau stress, and also prevent weakening of the compression buffering capacity due to excessively high plateau stress. This allows the non-vacuum closed-cell foam insulation and energy-absorbing layer to simultaneously perform shell support, load buffering, and crushing energy absorption functions under external impact loads, while reducing the risk of localized stress concentration or interface damage in the composite material pressure-bearing layer and metal lining structure.
[0050] Densification strain refers to the critical strain value corresponding to the transition from the plateau collapse stage to the densification compaction stage during the compression process of a non-vacuum closed-cell foam layer. Near this critical strain, the foam pore walls have undergone significant buckling, folding, rupture, or contact with each other, the pore space is significantly compressed, and the compressive stress of the foam material begins to rise rapidly. This embodiment requires a densification strain ≥0.4 (i.e., densification begins only when the compressive deformation reaches 40% or more), preferably ≥0.6. A higher densification strain helps to extend the plateau collapse deformation range of the foam layer, enabling the foam layer to continuously absorb external impact energy over a larger compression stroke. When a hydrogen storage container encounters external impact or extreme compressive loads, the non-vacuum closed-cell foam layer can provide a longer buffer stroke before entering the densification compaction stage, thereby reducing the risk of impact loads being directly transmitted to the composite material bearing layer and the metal liner structure, and improving the impact resistance safety of the hydrogen storage container.
[0051] This embodiment effectively blocks the gas convection heat transfer path between pores by limiting the closed-cell ratio of the non-vacuum closed-cell foam layer to ≥90%. Simultaneously, the closed-cell structure, together with the cell walls, provides compressive support during compression, enabling the foam layer to form a relatively stable plateau stress response under external compressive loads, reducing the risk of local instability or premature collapse. Furthermore, by controlling the density to 20-80 kg / m³... 3Within this range, a good balance is achieved between lightweight design, low-temperature insulation performance, and compression energy absorption capacity. This avoids the problem of insufficient support and energy absorption capacity due to excessively low density of the foam layer, while preventing increased structural mass and reduced insulation performance due to excessively high density. By limiting the apparent thermal conductivity to ≤0.050 W / (m·K) under ambient temperature characterization conditions (293-303 K) and ≤0.020 W / (m·K) under low-temperature service conditions (40-110 K), it is beneficial to reduce the environmental heat transfer of hydrogen storage containers during ambient temperature storage, transportation, or preparation for refueling. At the same time, it effectively reduces heat leakage from the environment to the hydrogen storage cavity under low-temperature and high-pressure hydrogen storage conditions, delaying the temperature rise and pressure increase of hydrogen in the storage cavity, thereby improving the non-venting retention of the hydrogen storage container. The system exhibits excellent time and low-temperature hydrogen storage stability. By limiting the crushing plateau stress to 0.2-3 MPa, premature crushing of the foam layer due to excessively low plateau stress is avoided, as is weakening of the compression buffering capacity due to excessively high plateau stress. This allows the foam layer of the hydrogen storage container to simultaneously function as a shell support, load buffer, and crushing energy absorption under external impact loads, while reducing the risk of impact loads being directly transmitted to the composite pressure-bearing layer and the metal liner structure. By limiting the densification strain to ≥0.4, the non-vacuum closed-cell foam layer is endowed with excellent energy absorption and buffering characteristics, enabling it to absorb external impact energy over a large compression stroke when encountering external impacts or extreme extrusion loads. This reduces the risk of localized stress concentration, interface damage, or structural failure in the composite pressure-bearing layer and the metal liner structure. The synergistic configuration of the above material parameters gives the non-vacuum closed-cell foam layer excellent thermal insulation performance, lightweight characteristics, structural support capacity, and impact energy absorption characteristics, ensuring the comprehensive performance and long-term reliability of the hydrogen storage container under wide temperature range, high pressure, and complex load conditions.
[0052] In a preferred embodiment, the thickness of the non-vacuum closed-cell foam layer is 5-80 mm, and the ratio of the thickness of the non-vacuum closed-cell foam layer to the outer radius of the hydrogen storage container is 0.03-0.50.
[0053] Specifically, setting the thickness of the non-vacuum closed-cell foam layer within the range of 5-80 mm is to ensure that the insulation thickness, compression buffer stroke, and structural mass of the foam layer match the actual dimensions of the hydrogen storage container. If the thickness is less than 5 mm, the insulation path provided by the non-vacuum closed-cell foam layer is too short, and the compression buffer stroke is insufficient, making it difficult to simultaneously meet the requirements of cryogenic insulation and external impact energy absorption. If the thickness is greater than 80 mm, although it can increase the insulation path and buffer stroke, it will increase the overall outer diameter, structural mass, and space occupation of the hydrogen storage container, reducing the payload capacity and layout adaptability of the UAV platform. It may also increase the risk of uneven thickness, internal defects, or interface debonding during the foaming, curing, or assembly process of the foam layer.
[0054] The ratio of the thickness of the non-vacuum closed-cell foam layer to the outer radius of the hydrogen storage container is 0.03-0.50. This ratio defines the proportion of the non-vacuum closed-cell foam layer thickness relative to the overall container size. When this ratio is less than 0.03, it indicates that the container size is large and the non-vacuum closed-cell foam layer is too thin, making it difficult to provide effective radial support and buffer energy absorption. When this ratio is greater than 0.50, the proportion of the foam layer relative to the container radius is too large, which will significantly increase the outer diameter, volume, and mass of the hydrogen storage container, which is detrimental to the lightweight design and space layout of the UAV hydrogen storage system. Controlling the ratio between 0.03 and 0.50 ensures that the non-vacuum closed-cell foam layer can meet the requirements of cryogenic insulation, crush energy absorption, interlayer support, and lightweight design in hydrogen storage containers of different specifications.
[0055] This embodiment effectively balances cryogenic insulation, impact energy absorption, and lightweight performance by limiting the thickness of the non-vacuum closed-cell foam layer to 5-80mm. Simultaneously, by limiting the ratio of the non-vacuum closed-cell foam layer thickness to the outer radius of the hydrogen storage container to 0.03-0.50, a reasonable proportion of the non-vacuum closed-cell foam layer thickness relative to the overall container size is ensured. This avoids situations where the foam layer is too thin (too small a ratio) leading to insufficient insulation path, buffer stroke, and interlayer support, or too large a ratio significantly increasing the outer diameter, volume, and structural mass of the hydrogen storage container, which would be detrimental to the spatial arrangement and payload capacity of the UAV platform. This synergistic control of thickness and ratio allows the non-vacuum closed-cell foam layer to be adapted to hydrogen storage containers of different specifications, achieving a good overall effect in terms of cryogenic insulation, crushing energy absorption, interlayer support, lightweighting, and molding process reliability.
[0056] In a preferred embodiment, the outer surface of the composite pressure-bearing layer is provided with an interface reinforcement structure, and a non-vacuum closed-cell foam layer is filled into the interface reinforcement structure by an in-situ foaming process, and forms a mechanical interlocking with the composite pressure-bearing layer after curing.
[0057] Specifically, to address the technical challenge of interfacial delamination between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer due to thermal stress or mechanical loads, an interface reinforcement structure is specially designed on the outer surface of the composite pressure-bearing layer. The non-vacuum closed-cell foam layer is directly filled into this interface reinforcement structure through an in-situ foaming process. After curing, it forms a strong mechanical interlocking (i.e., tenon or anchoring effect), thereby significantly improving the interfacial bonding strength.
[0058] This embodiment solves the technical problem of interface delamination between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer due to thermal stress or mechanical load by setting an interface reinforcement structure on the outer surface of the composite material pressure-bearing layer and directly filling the non-vacuum closed-cell foam layer into the interface reinforcement structure through an in-situ foaming process. After curing, a strong mechanical interlocking is formed, which significantly improves the interface bonding strength. This mechanical interlocking ensures that the foam core material and the pressure-bearing layer can maintain a strong interface connection under thermal stress cycling and external impact loads, avoiding structural delamination, decreased thermal insulation performance and load transfer interruption caused by interface failure. This ensures the structural integrity and long-term service reliability of the integrated sandwich structure of the hydrogen storage container.
[0059] In a preferred embodiment, the interface enhancement structure includes at least one of the following: surface roughening structure, microporous structure, shallow groove structure, mesh texture, local protrusions, fiber felt layer, or porous transition layer; wherein... When the interface enhancement structure is a surface roughening structure, the surface roughness of the surface roughening structure is 5-80 μm.
[0060] Specifically, the surface roughness of the surface-roughened structure is limited to 5~80μm, preferably 10~50μm, which is beneficial to improving the mechanical interlocking ability between the non-vacuum closed-cell foam insulation and energy-absorbing layer and the composite pressure-bearing layer. If the roughness is less than 5μm, the surface is too smooth, and the foam material is difficult to effectively penetrate into the micro-pits in the early stage of foaming, resulting in insufficient mechanical interlocking force. If the roughness is greater than 80μm, although the macroscopic interlocking depth increases, it is very easy to form foaming blind areas or micro-air gaps at the bottom of the grooves, which become weak points of interfacial stress concentration and reduce the overall bonding strength.
[0061] When the interface reinforcement structure is a shallow groove structure, the groove depth is 0.05-0.5mm, the groove width is 0.1-1.5mm, and the groove spacing is 0.5-5mm.
[0062] Specifically, the shallow groove structure provides a macroscopic mechanical interlocking space for the non-vacuum closed-cell foam layer. The limitation of groove depth and width allows the in-situ foamed material to enter the groove during foaming and expansion, forming a mechanical interlocking or anchoring effect after curing, thereby improving the interfacial bonding between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer. If the groove is too narrow or too shallow, the in-situ foamed material cannot fully enter the groove, easily leading to insufficient filling and weak interfacial mechanical interlocking. If the groove depth or width is too large, it may cause local stress concentration, which is detrimental to the structural integrity of the pressure-bearing layer. The limitation of groove spacing is to achieve a better balance between providing sufficient interfacial anchoring points and maintaining the effective load-bearing area of the composite pressure-bearing layer, avoiding severe weakening of the overall mechanical properties of the composite pressure-bearing layer due to excessively dense grooves.
[0063] When the interface reinforcement structure is a microporous structure, the pore size of the microporous structure is 20-500μm and the pore depth is 0.02-0.5mm.
[0064] Specifically, microporous structures are used to form a transitional anchoring interface on the outer surface of the composite pressure-bearing layer, intermediate between surface roughening and shallow groove structures. By limiting the pore size and depth of the microporous structure, in-situ foamed materials can enter the micropores during foaming expansion or interface wetting, forming microscale mechanical interlocking or anchoring after curing. This size range is beneficial for increasing the interfacial bonding area and interfacial shear resistance, while avoiding insufficient filling due to excessively small micropores, or local weakening and stress concentration on the surface of the pressure-bearing layer due to excessively large micropores. This reduces the risk of interfacial debonding, microcrack propagation, or delamination under thermal stress cycling and external impact loads.
[0065] This embodiment achieves multi-scale mechanical bonding and interface strengthening between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer by designing the interface reinforcement structure as at least one of the following: surface roughening structure, microporous structure, shallow groove structure, mesh texture, local protrusion, fiber felt layer, or porous transition layer. This improves the interfacial bonding strength, shear resistance, and peel resistance between the two layers, reducing the risk of interface debonding or delamination under thermal stress cycling and external impact load conditions, thereby ensuring the long-term structural integrity and service reliability of the integrated sandwich structure.
[0066] In a preferred embodiment, the interfacial shear strength between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥0.3MPa.
[0067] Specifically, the interfacial shear strength should be ≥0.3 MPa, preferably ≥0.5 MPa. During the hydrogen charging and discharging cycle of the hydrogen storage container, thermal stress and shear loads will be generated at the interface due to the difference in thermal expansion coefficients between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer. If the interfacial shear strength is lower than 0.3 MPa, microcracks are prone to initiation at the interface under service conditions such as low-temperature cycling or rapid hydrogen charging, which can then expand into macroscopic debonding, ultimately affecting the continuous support, thermal insulation, and buffering energy absorption functions of the non-vacuum closed-cell foam layer. The shear strength threshold of 0.3 MPa ensures that the non-vacuum closed-cell foam layer can serve as an effective buffer layer, maintaining good cooperative deformation capacity with the composite pressure-bearing layer when the hydrogen storage container is subjected to external impacts or shocks, reducing the risk of interfacial debonding, delamination, or localized failure, thereby ensuring continuous protection.
[0068] This embodiment effectively addresses the thermal stress and shear load generated during hydrogen charging and discharging cycles due to the difference in their thermal expansion coefficients by limiting the interfacial shear strength between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer to ≥0.3MPa. This avoids the risk of microcrack initiation and propagation into macroscopic debonding at the interface under service conditions such as low-temperature cycling or rapid hydrogen charging. It ensures that the non-vacuum closed-cell foam layer can maintain good cooperative deformation capability with the composite pressure-bearing layer when the hydrogen storage container is subjected to external impacts or shocks, reducing the risk of interfacial debonding, delamination, or local failure. This maintains the continuous support, heat insulation, and buffer energy absorption functions of the foam layer, ensuring the interfacial integrity and long-term service reliability of the integrated sandwich structure under thermo-mechanical coupling conditions.
[0069] In a preferred embodiment, after the hydrogen storage container undergoes ≥100 cycles of thermal cycling at a temperature between 77-300K, the interfacial shear strength retention rate between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥75%, and / or, the interfacial shear strength retention rate between the non-vacuum closed-cell foam layer and the composite shell is ≥75%.
[0070] Specifically, the composite material layer and the non-vacuum closed-cell foam layer have different coefficients of thermal expansion. During the rapid drop from 300K to 77K, alternating thermal stress is generated at the interface due to the inconsistent degree of shrinkage. After multiple thermal cycles, microcracks may form at the interface and gradually propagate. If the interfacial bonding is insufficient or the material is too brittle, the microcracks may connect to form macrocracks, leading to interfacial debonding and a significant decrease in strength retention. This embodiment ensures a strength retention rate of ≥75%, indicating that the interface maintains high load transfer capacity and bonding stability after repeated deep cryogenic cycles, thereby reducing the risk of interfacial delamination, debonding, or localized failure.
[0071] It should be noted that after curing, the foam material filling the interface-reinforced structure forms a gradient transition layer near the interface. This transition layer can alleviate the interfacial shear stress caused by the difference in thermal expansion coefficients through micro-interlocking, local deformation, and load dispersion, and reduce the risk of microcrack propagation and interface debonding during thermal cycling. Compared with bonding methods that rely solely on a smooth interface, the mechanical interlocking structure formed by in-situ foaming in this embodiment can provide a more stable interfacial load transfer path under low-temperature cycling and external impact loads, thereby ensuring a high strength retention rate.
[0072] In this embodiment, after ≥100 cycles of cryogenic cycling within a temperature range of 77-300K, the interfacial shear strength retention rate between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer, as well as between the non-vacuum closed-cell foam layer and the composite shell, is ≥75%. This demonstrates that each interface maintains high bonding stability and load transfer capacity even after repeated deep cryogenic cycling. Due to the differences in the thermal expansion coefficients of the materials in each layer, alternating thermal stress may be generated at the interface during cryogenic cycling, inducing microcracks, local debonding, or strength reduction. By limiting the strength retention rate as described above, and combining it with the mechanical interlocking or transition bonding area formed by in-situ foaming, the interfacial shear stress can be alleviated, reducing the risk of interfacial delamination, debonding, or local failure. This improves the structural integrity, thermal insulation stability, and service reliability of the integrated sandwich structure under cryogenic cycling and thermo-mechanical coupling conditions.
[0073] In a preferred embodiment, the composite material shell has a thickness of 0.3-3 mm and is configured to diffuse the impact load area to at least twice the impact contact area when subjected to a point impact.
[0074] Specifically, the composite material shell covers the outside of the non-vacuum closed-cell foam insulation and energy-absorbing layer, providing external constraint to the foam layer and playing a role in external protection, load diffusion, and stress homogenization. When the hydrogen storage container is subjected to an external local impact load, the composite material shell first bears the impact and, relying on its bending stiffness, in-plane stiffness, and interlayer load transfer capability, diffuses the local load originally concentrated on the initial impact contact area A0 to the surrounding area, forming an effective pressure-bearing area A acting on the non-vacuum closed-cell foam insulation and energy-absorbing layer. eff .
[0075] A eff / A0 is defined as the load diffusion ratio, and this ratio is limited to not less than 2, preferably not less than 4. If A eff If A0 is too small (close to 1), it indicates that the composite material shell has insufficient ability to diffuse local impact loads. The impact load is prone to concentrate near the initial contact area, which may lead to local damage to the composite material shell, premature crushing of the non-vacuum closed-cell foam layer, or stress concentration at the interface, thereby weakening the thermal insulation and energy absorption protection of the foam layer; if A effA / A0 value of 2 or higher (especially 4 or higher) indicates that the composite shell can utilize its bending stiffness, in-plane stiffness, and interlaminar load transfer capability to diffuse external local impact loads into distributed loads with a larger effective area, transferring them to the non-vacuum closed-cell foam layer, causing the foam layer to undergo compressive deformation over a larger range. This improves the plateau crushing energy absorption efficiency of the non-vacuum closed-cell foam insulation layer and reduces the risk of impact loads being directly transferred to the composite pressure-bearing layer and the metal lining structure. For example, when an external spherical impactor acts on the composite shell, the shell can diffuse the local impact load within the initial contact area to the surrounding area, making the effective pressure-bearing area of the non-vacuum closed-cell foam layer larger than the initial contact area. This allows the foam layer to absorb impact energy primarily through compressive deformation, reducing the risk of local shear tearing or point pressure failure.
[0076] To achieve the aforementioned load diffusion effect, the thickness of the composite material shell is limited to 0.3-3 mm, preferably 0.5-2.5 mm, and more preferably 1-2 mm. Within this limited thickness range, combined with the layup of high-modulus fibers (such as carbon fiber or glass fiber), A can be achieved with minimal weight loss. eff / A0 exhibits excellent diffusion performance.
[0077] This embodiment limits the thickness of the composite material shell to 0.3-3 mm and configures it to extend the effective pressure-bearing area transferred to the non-vacuum closed-cell foam insulation energy-absorbing layer to at least twice the initial impact contact area when subjected to external local impact loads. This allows the composite material shell to not only serve as the outermost protective structure of the hydrogen storage container but also to play a role in load diffusion and stress homogenization. This thickness range, combined with the high-modulus fiber layup structure, can improve the load diffusion and local protection capabilities of the composite material shell with a relatively small increase in mass. When the hydrogen storage container is subjected to external local impact loads, the composite material shell can rely on its bending stiffness, in-plane stiffness, and interlayer load transfer capability to diffuse the local load concentrated on the initial contact area to the surrounding area and transfer it to the non-vacuum closed-cell foam layer as a distributed load with a larger effective area. As a result, the foam layer can undergo compressive deformation over a larger range, fully utilizing its plateau crushing energy absorption function, reducing the risk of local damage to the shell, premature crushing of the foam layer, or interface stress concentration due to excessive local load concentration, thereby reducing the possibility of impact loads being directly transferred to the metal liner structure and the composite material pressure-bearing layer.
[0078] Figure 1 A flowchart illustrating a method for manufacturing a hydrogen storage container according to an embodiment of this application is provided. This process may include the following steps: Step S1: Provide a metal liner structure.
[0079] Specifically, the metal liner is preferably made of aluminum alloy (such as 6061-T6), and is made into a seamless inner liner through spinning or stamping processes.
[0080] Step S3: Fibers are wound onto the outer surface of the metal liner structure to form a composite material bearing layer, and a first curing treatment is performed.
[0081] Specifically, before fiber winding, the outer surface of the metal liner structure is sandblasted or chemically treated to improve the interfacial bonding ability of the outer surface of the metal liner structure and enhance the bonding stability between it and the composite pressure-bearing layer. Fibers are then wound onto the outer surface of the metal liner structure. High-strength carbon fiber reinforced low-temperature resistant resin-based composite material is preferably used. The fiber winding method includes helical winding and circumferential winding. The helical winding layer is used to bear the axial load of the hydrogen storage container and form a continuous load-bearing transition in the end cap section, while the circumferential winding layer is used to bear the circumferential stress in the cylinder section. The helical winding angle can be selected from ±10° to ±35°, for example, ±14.5°; the circumferential winding angle can be selected to be close to 90° to improve the circumferential load-bearing capacity of the cylinder section. After winding, a first curing treatment is performed to allow the low-temperature resistant resin matrix to reach a preset degree of curing, thereby forming a composite pressure-bearing layer covering the outside of the metal liner structure. The preset degree of curing can be a gel state, a semi-cured state, or a fully cured state, preferably a cured state that can maintain the shape stability of the winding layer and meet the requirements of the subsequent foam layer molding process. After the first curing process, the metal liner structure and the composite pressure-bearing layer form a metal liner-composite pressure-bearing layer semi-finished part, which is used to subsequently form a non-vacuum closed-cell foam heat insulation and energy absorption layer and a composite shell.
[0082] Step S5: A non-vacuum closed-cell foam layer is formed on the outside of the cured composite material pressure-bearing layer.
[0083] Specifically, this step preferably employs an in-situ foaming process. After mixing the foam raw materials to form a foaming system, it is applied to the outer surface of the composite material's pressure-bearing layer via pouring, spraying, or injection. The layer is then placed in a pre-set mold, allowing the foaming system to expand and solidify between the mold and the composite material's pressure-bearing layer, forming a continuous foam layer covering the outer surface of the composite material's pressure-bearing layer. During the foaming and curing process, the foaming system can penetrate the rough, microporous, or shallow groove structures on the outer surface of the composite material's pressure-bearing layer, forming a mechanical interlocking or anchoring effect after curing. Simultaneously, the foaming system can interact with the polar groups, residual active groups, or surface treatment layers on the surface of the composite material's pressure-bearing layer, forming a tight interfacial bond. The resulting non-vacuum closed-cell foam layer has a closed-cell structure with a closed-cell rate ≥90%, providing low-temperature insulation, interlayer support, and crushing energy absorption without relying on an independent vacuum insulation cavity.
[0084] Step S7: Fibers are wound onto the outer surface of the non-vacuum closed-cell foam layer to form a composite material shell, and a second curing treatment is performed to make the composite material shell, the non-vacuum closed-cell foam layer and the composite material pressure-bearing layer form an integrated sandwich structure.
[0085] Specifically, the reinforcing fibers of the composite shell can be carbon fiber, glass fiber, aramid fiber, or hybrid fibers thereof, used to provide external constraint on the foam layer and to provide external protection, load diffusion, and impact resistance. After the composite shell is formed, a second curing process is performed. During this process, the resin matrix undergoes cross-linking and curing to reach the preset curing degree. Simultaneously, a bonding interface is formed through resin impregnation, interfacial bonding, surface mechanical interlocking, or local interfacial penetration, thereby improving the interfacial connection stability between the composite shell and the foam layer. After the second curing, the composite shell, the non-vacuum closed-cell foam insulation and energy-absorbing layer, and the composite pressure-bearing layer together form an integrated sandwich structure. Compared with a split assembly structure, this integrated sandwich structure can reduce the risks of interlayer relative slippage, local debonding, or discontinuous interfacial load transfer. It allows the composite shell to diffuse external local impact loads to the non-vacuum closed-cell foam layer, and the foam layer to undergo compressive deformation and crushing energy absorption within a larger equivalent contact area, thereby improving the external protection capability, thermal insulation stability, and impact resistance of the hydrogen storage container.
[0086] The manufacturing method of the hydrogen storage container provided in this embodiment involves using a spinning or stamping process to create a seamless aluminum alloy liner, forming a hydrogen storage cavity and providing an airtight barrier; improving the interfacial bonding between the metal liner structure and the composite pressure-bearing layer by sandblasting or chemical treatment of the outer surface of the metal liner; and using a high-strength carbon fiber reinforced low-temperature resistant resin-based composite material, spirally and circumferentially wound at a preset layup angle to form a composite pressure-bearing layer, which is then subjected to a first curing treatment to form a semi-finished metal liner-composite pressure-bearing layer component to bear the main pressure load under low-temperature and high-pressure conditions; and using an in-situ foaming process to form a non-vacuum closed-cell foam with a closed-cell rate of ≥90% on the outside of the composite pressure-bearing layer. The first layer utilizes a foaming reaction to physically anchor or chemically bond the foam material to the surface of the pressure-bearing layer, forming a tight interfacial connection. Under non-vacuum conditions, this provides cryogenic insulation, sandwich support, and crush-absorbing energy, while also serving as a core layer supporting the inner and outer composite material layers. A composite material shell is formed by winding fibers around the outer surface of the foam layer and undergoing a second curing treatment. This integrates the composite material shell, the non-vacuum closed-cell foam insulation and energy-absorbing layer, and the composite pressure-bearing layer into an integrated sandwich structure. This structure helps reduce the risks of interlayer slippage, local debonding, and discontinuous interfacial load transfer, enabling the hydrogen storage container to simultaneously possess gas-tight barrier, high-pressure load-bearing capacity, non-vacuum cryogenic insulation, sandwich support, and impact-resistant energy absorption functions. This multi-step synergistic manufacturing process achieves layer-by-layer forming and integrated connection of the hydrogen storage container from the gas-tight liner, pressure-bearing layer, insulation and energy-absorbing core layer to the outer protective shell. This improves the interfacial bonding strength and structural synergy, and gives the hydrogen storage container high-pressure load-bearing capacity, cryogenic insulation, sandwich support, and impact protection.
[0087] In a preferred embodiment, both the first curing treatment and the second curing treatment employ multi-stage temperature-increasing curing; the multi-stage temperature-increasing curing includes: First stage: Incubate at 353-363K for 0.5-1 hour; Second stage: Heat to 383-393K and hold for 2-3 hours; Third stage: Heat to 403-413K and hold for 2-3 hours; The heating rate of the first curing treatment and the second curing treatment was controlled at 274-276 K / min between each stage.
[0088] Specifically, the resin system is held at 353-363 K for 0.5-1 h, which is the initial flow, wetting, and gelation stage. Within this temperature range, the viscosity of the resin system first decreases and then gradually increases, which is beneficial for the resin to further wet the fiber bundles and for the gradual discharge of any trace gases and volatiles that may remain during the winding process. If the heating rate is too fast or the process directly enters a higher temperature stage, the resin surface may gel or solidify prematurely, affecting the discharge of internal gases and thus increasing the risk of micropores or curing defects within the composite material layer.
[0089] The temperature is increased to 383-393 K at a rate of 274-276 K / min and held for 2-3 hours. This stage is the main cross-linking and curing stage of the resin system. Heating to 383-393 K accelerates the curing reaction rate. Holding for 2-3 hours improves the degree of curing of the resin matrix and is beneficial to the temperature uniformity of the composite material's bearing layer or outer shell along the thickness direction, reducing the risk of residual stress, curing gradient, or localized deformation caused by differences in the degree of curing inside and outside the composite material.
[0090] The temperature is increased to 403-413 K at a rate of 274-276 K / min and held for 2-3 hours. This is the post-curing stage, which promotes further reaction of residual active groups, improves the cross-linking degree and stability of the resin network structure, and thus improves the mechanical properties, interfacial bonding stability, and service reliability of the composite layer. The post-curing temperature of 403-413 K is more conducive to balancing the full curing of the resin with the thermal stability of the non-vacuum closed-cell foam layer, reducing the risk of thermal shrinkage, collapse, or interfacial debonding of the foam layer.
[0091] This embodiment employs multi-stage heating and curing in both the first and second curing processes, limiting the temperature, holding time, and heating rate at each stage. This achieves precise control of the crosslinking reaction of the resin matrix and optimization of the curing quality within the composite material layer. The multi-stage heating and curing process, through the synergistic effect of gradient temperature control and controlled heating rate, effectively reduces the risks of micropores, uneven curing, residual stress concentration, and localized deformation within the composite material layer. It improves the interlayer bonding stability, dimensional retention, and mechanical properties between the pressure-bearing composite layer and the outer shell, ensuring the structural reliability and service safety of the hydrogen storage container under low-temperature, high-pressure conditions.
[0092] To better explain and facilitate understanding of this application, a detailed description of its specific embodiments is provided below. Unless otherwise specified in the embodiments, all raw materials used in the embodiments of this application are purchased commercially.
[0093] Example 1 In specific application scenarios of hydrogen fuel cell systems for drones Figure 2 Example 1 provides a schematic diagram of a cryogenic high-pressure hydrogen storage container for use in a drone hydrogen fuel cell system. This hydrogen storage container achieves an integrated design of thermal insulation and shock resistance. Its design temperature is 80K, design pressure is 40MPa, and internal volume is approximately 12L. From the inside out, the hydrogen storage container comprises a metal inner liner structure 1, a composite material pressure-bearing layer 2, a non-vacuum closed-cell foam layer 3, and a composite material outer shell 4.
[0094] The interlayer space between the composite pressure-bearing layer 2 and the composite shell 4 is continuously filled by a non-vacuum closed-cell foam layer 3. Except for the closed-cell cavities of the non-vacuum closed-cell foam layer 3 itself, there is no independent sealed cavity within this interlayer space for forming vacuum insulation. Under operational conditions, the difference between the gas pressure in the interlayer space and the ambient gas pressure outside the hydrogen storage container does not exceed 5 kPa. The non-vacuum closed-cell foam layer 3 is not a filling material in traditional vacuum interlayers, but rather a functional layer that simultaneously undertakes the functions of cryogenic insulation, impact energy absorption, and support of the interlayer core material.
[0095] 1. Metal lining structure The metal liner structure 1 is made of 6061 aluminum alloy and includes a cylindrical body section and ellipsoidal end caps located at both ends of the body section. The outer diameter of the body section is approximately 200 mm, the total length of the hydrogen storage container is approximately 540 mm, and the internal volume is approximately 12 L. The metal liner structure 1 is used to form the hydrogen storage cavity, prevent hydrogen permeation, and serve as a core mold for the composite pressure-bearing layer 2, which is wound and formed.
[0096] In the preferred embodiment, the 6061 aluminum alloy liner is strengthened using a deformation heat treatment process to improve its yield strength, elastic strain limit, and pressure cyclic fatigue performance. The deformation heat treatment process includes solution treatment, pre-deformation treatment, and two-stage aging treatment. For example, the solution treatment temperature is 793~813K, held for 0.5h~2h, and then water-cooled; the pre-deformation amount is 20%~50%; the two-stage aging includes low-temperature pre-aging and high-temperature final aging. This treatment helps reduce the plastic accumulation of the metal liner during pressure cycling.
[0097] In this embodiment, the metal liner structure 1 has a wall thickness of approximately 2 mm and a mass of approximately 1.8 kg. This thickness satisfies the requirements for manufacturing, airtightness, and rigidity as a winding mandrel, while avoiding an excessive increase in the container's mass. It should be noted that the metal liner structure 1 can also be made of other metal materials suitable for low-temperature, high-pressure hydrogen environments, such as other 6-series aluminum alloys, stainless steel, or titanium alloys.
[0098] 2. Composite material bearing layer Fibers are wound onto the outer surface of the metal liner structure 1 to form a composite pressure-bearing layer 2, which is then subjected to a first curing treatment. The composite pressure-bearing layer 2 is used to bear the main pressure load generated by low-temperature, high-pressure hydrogen in the hydrogen storage cavity.
[0099] In this embodiment, the composite pressure-bearing layer 2 is made of T700S grade carbon fiber reinforced low-temperature resistant epoxy resin matrix composite material, formed by a combination of helical winding and circumferential winding. The helical winding angle is determined based on the radius of the container's electrode orifice and the radius of the cylinder body, and can be in the range of ±10° to ±35°; the circumferential winding angle is close to 90°. For example, if the radius R of the container cylinder section is 100 mm and the radius R0 of the electrode orifice is 25 mm, the helical winding angle α is estimated to be approximately 14.5° using α=arcsin(R0 / R). Taking into account the design pressure, fiber strength, resin content, fiber volume fraction, manufacturing deviation, and safety margin, the cured thickness of the composite pressure-bearing layer 2 is approximately 4.1 mm, and its mass is approximately 1.9 kg.
[0100] The first curing process employs a multi-stage heating curing method, for example: heating at a rate of 274-276K / min to 353-363K and holding for 0.5-1h; then heating to 383-393K and holding for 2-3h; and finally heating to 403-413K and holding for 2-3h.
[0101] Before forming the non-vacuum closed-cell foam layer 3, the outer surface of the cured composite pressure-bearing layer 2 undergoes interface reinforcement treatment. Interface reinforcement treatment includes at least one of the following: mechanical grinding, sandblasting, plasma activation, laser texturing, shallow trenching, microporous treatment, fiber mat laying, or setting a mesh texture. Through these treatments, the subsequent foaming material can penetrate into the micropores or rough structure of the pressure-bearing layer's outer surface, thereby forming mechanical interlocking or interface bonding, and improving the interfacial bonding strength.
[0102] 3. Non-vacuum closed-cell foam layer A non-vacuum closed-cell foam layer 3 is formed on the outer side of the cured composite pressure-bearing layer 2. In this embodiment, rigid closed-cell polyurethane foam is used, which is directly formed on the outer surface of the composite pressure-bearing layer 2 through an in-situ spraying foaming process, with a spraying pressure of 5~10MPa. During the expansion process, the foaming material enters the micropores or rough structure on the outer surface of the composite pressure-bearing layer 2, forming a mechanical interlocking.
[0103] In this embodiment, the thickness of the non-vacuum closed-cell foam layer 3 is approximately 40 mm, and its mass is approximately 0.75 kg. After curing, the non-vacuum closed-cell foam layer 3 meets the following parameters: closed-cell rate of approximately 92%; density of approximately 32 kg / m³. 3 The apparent thermal conductivity at room temperature is not greater than 0.028 W / (m·K); the apparent thermal conductivity at liquid nitrogen temperature of 77 K is not greater than 0.0095 W / (m·K); the crushing platform stress is not less than 0.65 MPa; and the densification strain is not less than 0.60.
[0104] The thickness of the non-vacuum closed-cell foam layer 3 is determined jointly based on the insulation requirements and the impact energy absorption requirements. For example, when the equivalent drop mass of the UAV's hydrogen storage container is 7 kg and the impact velocity is 5 m / s, the impact kinetic energy is approximately 87.5 J. Based on formula E... f =σ p ×A eff ×δ max (where σ) p To compensate for the crushing platform stress, A eff δ represents the effective pressure-bearing area (i.e., the area subjected to impact load) after diffusion through the composite material shell 4. max (For densification strain), when the thickness of the non-vacuum closed-cell foam layer 3 is 40mm, the theoretical energy that can be absorbed is about 443J, which can provide a large energy absorption margin for the ground impact condition of the UAV hydrogen storage container and reduce the risk of the impact load being directly transmitted to the composite material pressure layer 2 and the metal liner structure 1.
[0105] 4. Composite material shell After the non-vacuum closed-cell foam layer 3 has cured and stabilized, fibers are wound around its outer surface to form a composite material shell 4, and a second curing treatment is performed. The composite material shell 4 is used to provide external constraint for the non-vacuum closed-cell foam layer 3 and to diffuse the local impact load from the initial contact area (impact contact area) to the effective pressure area (force-bearing area of the impact load), while protecting the non-vacuum closed-cell foam layer 3 from damage by the external environment.
[0106] In this embodiment, the composite material shell 4 is made of carbon fiber reinforced epoxy resin matrix composite material with a thickness of approximately 2 mm and a weight of approximately 1.7 kg. The layup is mainly composed of circumferential layers (accounting for 70%~90%), and ±15° to ±30° spiral layers are set to improve the overall continuity of the shell, shear resistance, and local impact resistance. During the winding process, the winding tension of the composite material shell 4 is approximately 20%~40% of the winding tension of the composite material bearing layer 2 to avoid excessive compression of the foam layer.
[0107] The second curing process also employs multi-stage temperature curing. After curing, the composite material shell 4, the non-vacuum closed-cell foam layer 3, and the composite material pressure-bearing layer 2 form an integrated sandwich structure. In this structure, the composite material shell 4 serves for load diffusion and external constraint, the non-vacuum closed-cell foam layer 3 serves for thermal insulation and crushing energy absorption, and the composite material pressure-bearing layer 2 serves to bear the internal pressure load. The synergy of these three components enables the hydrogen storage container for UAVs to meet the requirements of cryogenic insulation, high-pressure bearing, impact resistance, and lightweight design.
[0108] 5. Mass hydrogen storage density In this embodiment, the mass hydrogen storage density of the hydrogen storage container is calculated according to the following formula: Where ω is the mass hydrogen storage density, The mass of hydrogen that the hydrogen storage container can store is m0, where m0 is the mass of the empty container (including the mass of the metal inner lining structure 1, the composite pressure-bearing layer 2, the non-vacuum closed-cell foam layer 3, the composite outer shell 4, and the necessary interface components).
[0109] Under conditions of a design temperature of 80K, a design pressure of 40MPa, and an internal volume of approximately 12L, the mass of hydrogen that can be stored is... The total mass is approximately 0.79 kg. The empty container mass m0 is approximately 6.49 kg (including 1.8 kg for the metal liner, 1.94 kg for the composite pressure-bearing layer, 0.75 kg for the non-vacuum closed-cell foam layer, 1.7 kg for the composite shell, and 0.3 kg for the interfaces and accessories). Calculations show that the mass hydrogen storage density of the hydrogen storage container in this embodiment is approximately 10.9%, meeting the design target of greater than 10%. By optimizing the interface mass and further reducing the mass of the shell and liner, the mass hydrogen storage density can reach or exceed 12%.
[0110] The cryogenic insulation performance and non-venting retention capability of Example 1 above were verified: Test methods and conditions: The hydrogen storage container prepared in Example 1 was pre-cooled and filled with low-temperature hydrogen or a low-temperature equivalent medium for heat leakage testing. During the test, the hydrogen storage container was placed in an environment of 298K, and the changes in internal temperature and pressure over time were recorded in real time. The equivalent heat leakage and apparent heat leakage flux were calculated based on the thermophysical properties of the medium.
[0111] Apparent heat leakage heat flux density verification: The external surface area of the hydrogen storage container is approximately 0.39 m². 2 The thickness of the non-vacuum closed-cell foam layer is 40 mm. Tests show that the apparent thermal conductivity of this non-vacuum closed-cell foam layer is no greater than 0.028 W / (m·K) at room temperature and no greater than 0.0095 W / (m·K) at liquid nitrogen temperature of 77 K.
[0112] Based on the above parameters, calculations and tests show that, under ambient temperatures not exceeding 333K, the apparent heat leakage flux density of the hydrogen storage container is approximately 80W / m³. 2 .
[0113] Verification of No-Vent Holding Time: Under cryogenic and high-pressure hydrogen storage conditions, the test showed that the no-vent holding time of the hydrogen storage container before rising from the initial operating pressure to the safe release pressure was approximately 59 hours. This test result fully verifies that the hydrogen storage container of this embodiment can meet the performance requirement of a no-vent holding time of ≥12 hours before reaching the safe release pressure, and that within the actual usage window of the UAV, the non-vacuum closed-cell foam layer can provide sufficient and excellent cryogenic holding capability.
[0114] It is important to note that for cryogenic high-pressure hydrogen storage containers, their thermal insulation performance should not be evaluated solely based on the pressure drop rate of the gas at room temperature and high pressure. This application employs a comprehensive evaluation index, which systematically assesses the performance through equivalent heat loss, apparent heat loss heat flux density, internal temperature rise rate, pressure rise rate, and the non-venting holding time before reaching the safe release pressure. This approach more accurately and objectively reflects the true thermal insulation performance of the hydrogen storage container under complex operating conditions.
[0115] Impact energy absorption was verified for Example 1 above: Test methods and conditions: The hydrogen storage container prepared in Example 1 was placed horizontally and dropped freely onto a concrete surface at a speed of 5 m / s to simulate the local impact condition of a drone hitting the ground after being cushioned by a parachute during an accidental crash. Before and after the drop test, the hydrogen storage container underwent visual inspection, dimensional measurement, airtightness testing, and non-destructive testing of the composite material pressure-bearing layer.
[0116] Test results: After drop test, the composite material shell showed acceptable surface indentations in some areas, but no through cracks occurred; the maximum compression depth of the non-vacuum closed-cell foam layer was about 16 mm, which is less than the allowable compression depth corresponding to the densification strain of the non-vacuum closed-cell foam layer thickness of 40 mm, and it has not reached the fully densified state; no obvious damage was detected in the composite material bearing layer and the metal lining structure 1; and the airtightness test was qualified.
[0117] The above test results fully demonstrate that when subjected to drop impact, the composite material shell can effectively diffuse the local impact load to a larger area of the non-vacuum closed-cell foam layer; the non-vacuum closed-cell foam layer can absorb a large amount of impact energy through pore wall buckling, plateau crushing and shear deformation, thereby effectively reducing the direct transmission of impact load to the composite material bearing layer and metal lining structure 1, and playing an excellent buffering and protective role.
[0118] Low-temperature cycling and interface integrity verification were performed on Example 1 above: Test methods and conditions: The hydrogen storage container prepared in Example 1 was placed in an environmental test chamber for a thermal cycling test between room temperature and liquid nitrogen temperature (or a preset low-temperature environment). Each cycle included a room temperature holding phase, a liquid nitrogen temperature holding phase, and a return to room temperature phase. In this example, the cumulative number of cycles was set to 100.
[0119] Interface integrity check results: After the test, a comprehensive inspection was carried out on the appearance of the hydrogen storage container, the integrity of the non-vacuum closed-cell foam layer, the integrity of the composite material shell, and the interface bonding between each layer.
[0120] The results showed that: the composite material shell did not show obvious cracking; the non-vacuum closed-cell foam layer did not show obvious pulverization, collapse or large-area debonding; there was no through-interface separation between the composite material pressure-bearing layer, the non-vacuum closed-cell foam layer and the composite material shell; and the air tightness test was qualified.
[0121] The test results above fully demonstrate that the interface reinforcement structure on the outer surface of the composite pressure-bearing layer and the mechanical interlocking relationship formed by the in-situ foaming of the non-vacuum closed-cell foam layer significantly improve the low-temperature cycling stability between the non-vacuum closed-cell foam layer and the composite pressure-bearing layer, and ensure the overall impact resistance of the hydrogen storage container under complex thermal environments.
[0122] Comparative Example 1 The system employs a conventional vacuum insulation structure commonly found in cryogenic, high-pressure hydrogen storage containers. This structure includes a metal liner, a composite pressure-bearing layer, a vacuum interlayer, multiple layers of insulation material, and a vacuum outer shell. The metal liner and composite pressure-bearing layer bear the pressure load generated by the cryogenic, high-pressure hydrogen; the vacuum interlayer and multiple layers of insulation material reduce heat leakage from the environment to the hydrogen storage cavity; and the vacuum outer shell forms and maintains the vacuum interlayer space.
[0123] For the same internal volume and similar external dimensions, traditional vacuum insulation structures require additional outer shells and vacuum maintenance components, significantly increasing the weight and manufacturing complexity of the container system. Furthermore, under drop or vibration conditions, if the vacuum sealing structure is damaged, leading to a decrease in vacuum level, it will cause a degradation in insulation performance, resulting in increased heat leakage and faster pressure rise.
[0124] Compared with the comparative example, Example 1 eliminates the vacuum interlayer, vacuum extraction port, vacuum valve, pressure vacuum gauge and vacuum maintenance accessories, and adopts a non-vacuum closed-cell foam layer to achieve integrated low-temperature insulation and impact-resistant energy absorption, which is more suitable for lightweight and drop-impact resistant applications of UAVs.
[0125] Comparative Example 2 A foam-insulated liquid hydrogen container structure is adopted. This structure includes an inner liner, a foam insulation layer, and an outer support layer. The inner liner is made of approximately 2mm thick stainless steel, and the foam insulation layer can be made of closed-cell foam materials such as polyurethane for cryogenic liquid hydrogen storage. This type of structure is mainly designed for low-pressure liquid hydrogen storage, with typical storage pressures ranging from 0.9MPa to 1.2MPa and storage temperatures from 15K to 32K. The foam insulation layer thickness is 10mm to 20mm. Its key technical aspects include cryogenic liquid hydrogen storage, liquid hydrogen-gas phase balance, gas-liquid inlet / outlet structure, adaptability of the inner liner material, and hydrogen barrier properties.
[0126] Under the same internal volume conditions, foam-insulated liquid hydrogen containers can store a larger mass of hydrogen due to the higher density of liquid hydrogen; however, their operating temperature is usually lower than that of cryogenic high-pressure hydrogen containers, resulting in a larger ambient temperature difference and higher requirements for the thermal conductivity, thickness, interface thermal bridge control, and evaporation loss control of the insulation layer. Furthermore, the foam insulation layer of this type of container is typically not designed as a crushable energy-absorbing core material constrained by the composite material shell, nor are design constraints established for the crushing platform stress, densification strain, and energy absorption of the foam layer for drone descent, drop, or localized impact loads.
[0127] Compared to the comparative example, Example 1 does not simply use foam material as the cryogenic insulation layer. Instead, a non-vacuum closed-cell foam layer is continuously filled between the composite pressure-bearing layer and the composite shell, allowing it to function as an insulation layer, a crushing energy-absorbing layer, and a sandwich core material. Example 1 is designed for cryogenic high-pressure hydrogen storage scenarios for UAVs. By constraining the non-vacuum closed-cell foam layer and diffusing local impact loads through the composite shell, the non-vacuum closed-cell foam layer can absorb energy during ground impact through pore wall buckling, platform crushing, shear deformation, and densification. Therefore, Example 1 achieves a better overall balance between a longer non-venting retention time, high-quality hydrogen storage density, and impact resistance, making it more suitable for lightweight cryogenic high-pressure hydrogen storage scenarios for UAVs.
[0128] To further illustrate the technical effects of this application, a comprehensive comparison of Example 1 with Comparative Examples 1 to 2 in terms of thermal insulation performance, energy absorption performance, and lightweight parameters was made, as shown in the table below: As shown in the table above, the embodiments of this application achieve a better overall balance between high-quality hydrogen storage density, long non-venting retention time, and impact energy absorption capability. Specifically: the mass hydrogen storage density of the embodiments of this application reaches 10.9%, meeting the lightweight parameter limit of more than 10%; the non-venting retention time reaches 59 hours, meeting the adiabatic retention requirement of not less than 12 hours (preferably not less than 24 hours); and the equivalent energy absorption reaches 443 J, meeting the impact energy absorption requirement of not less than 200 J.
[0129] Compared with traditional vacuum-insulated cryogenic high-pressure hydrogen storage containers (Comparative Example 1), this application effectively reduces the mass of the empty container and improves its shock resistance and energy absorption capacity; compared with foam-insulated liquid hydrogen containers (Comparative Example 2), this application has a longer non-venting retention time and more stable cryogenic high-pressure service adaptability. Therefore, the hydrogen storage container provided by this application is more suitable for the comprehensive requirements of lightweight, shock resistance, and long storage time in the application scenario of continuous hydrogen supply from UAVs.
[0130] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0131] The above description is merely an embodiment of this application and is not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.
[0132] Although embodiments of this application have been described in conjunction with the accompanying drawings, those skilled in the art can make various modifications and variations without departing from the spirit and scope of this application, and such modifications and variations all fall within the scope defined by the appended claims.
Claims
1. An integrated cryogenic high-pressure hydrogen storage container for unmanned aerial vehicles (UAVs), characterized in that, The hydrogen storage container is used in a drone hydrogen fuel cell system, and the hydrogen storage container comprises, from the inside out: A metal liner structure is used to form a hydrogen storage cavity; A composite material bearing layer covers the outside of the metal liner structure; A non-vacuum closed-cell foam layer fills and covers the outside of the composite material pressure-bearing layer; A composite material shell covers the outside of the non-vacuum closed-cell foam layer; The composite material pressure-bearing layer, the non-vacuum closed-cell foam layer, and the composite material shell constitute an integrated sandwich structure. The non-vacuum closed-cell foam layer, as the core material of the integrated sandwich structure, is configured to provide both thermal insulation and impact resistance. The non-vacuum closed-cell foam layer fills the interlayer space between the composite material pressure-bearing layer and the composite material shell; wherein, apart from the closed-cell cavities of the non-vacuum closed-cell foam layer itself, there is no independent sealed cavity in the interlayer space for forming vacuum insulation, and the difference between the gas pressure in the interlayer space and the external ambient gas pressure of the hydrogen storage container is ≤5kPa; the non-vacuum closed-cell foam layer is in a non-vacuum state, which means that the non-vacuum closed-cell foam layer is not maintained in an insulating state by vacuuming during the preparation and curing process, and the cells of the non-vacuum closed-cell foam layer are filled with atmospheric pressure gas; the non-vacuum closed-cell foam layer has an apparent thermal conductivity ≤0.020W / (m·K) at a temperature of 40-110K, a crushing plateau stress of 0.2-3MPa, and a densification strain ≥0.4; the thickness of the composite material shell is 0.3-3mm, and it is configured to diffuse the impact load area to at least twice the impact contact area when subjected to point impact.
2. The hydrogen storage container according to claim 1, characterized in that, The material parameters of the non-vacuum closed-cell foam layer meet the following requirements: Closed-cell ratio ≥90%; Density is 20-80 kg / m³ 3 ; Under the condition of temperature 293-303K, the apparent thermal conductivity is ≤0.050W / (m•K).
3. The hydrogen storage container according to claim 1, characterized in that, The thickness of the non-vacuum closed-cell foam layer is 5-80 mm, and the ratio of the thickness of the non-vacuum closed-cell foam layer to the outer radius of the hydrogen storage container is 0.03-0.
50.
4. The hydrogen storage container according to claim 1, characterized in that, The outer surface of the composite pressure-bearing layer is provided with an interface reinforcement structure. The non-vacuum closed-cell foam layer is filled into the interface reinforcement structure by an in-situ foaming process and forms a mechanical interlock with the composite pressure-bearing layer after curing.
5. The hydrogen storage container according to claim 4, characterized in that, The interface enhancement structure includes at least one of the following: surface roughening structure, microporous structure, shallow groove structure, mesh texture, local protrusions, fiber felt layer, or porous transition layer; wherein... When the interface enhancement structure is a surface roughening structure, the surface roughness of the surface roughening structure is 5-80 μm; When the interface enhancement structure is a shallow groove structure, the groove depth is 0.05-0.5mm, the groove width is 0.1-1.5mm, and the groove spacing is 0.5-5mm. When the interface enhancement structure is a microporous structure, the pore diameter of the microporous structure is 20-500 μm and the pore depth is 0.02-0.5 mm.
6. The hydrogen storage container according to claim 4, characterized in that, The interfacial shear strength between the composite material pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥0.3MPa.
7. The hydrogen storage container according to claim 4, characterized in that, After the hydrogen storage container undergoes ≥100 cycles of thermal cycling at a temperature between 77-300K, the interfacial shear strength retention rate between the composite pressure-bearing layer and the non-vacuum closed-cell foam layer is ≥75%, and / or the interfacial shear strength retention rate between the non-vacuum closed-cell foam layer and the composite shell is ≥75%.
8. The hydrogen storage container according to claim 1, characterized in that, The performance indicators of the hydrogen storage container include: The design temperature is 40-110K; The design pressure is 10-70 MPa; Mass hydrogen storage density ≥10%; The non-venting holding time before reaching the safe relief pressure is ≥12 hours; Under ambient temperature ≤333K, the apparent heat leakage flux density is ≤100W / m³. 2 ; The theoretical energy absorption of the non-vacuum closed-cell foam layer is ≥200J.
9. The hydrogen storage container according to claim 1, characterized in that, The metal liner structure is made of a low-temperature hydrogen-compatible metal material, which is selected from at least one of 6061 aluminum alloy, 6063 aluminum alloy, 5083 aluminum alloy, 304L stainless steel, 316L stainless steel or TC4 titanium alloy. The composite pressure-bearing layer is made of carbon fiber reinforced low-temperature resistant resin matrix composite material, which is formed by mixing carbon fiber and resin material. The carbon fiber is selected from at least one of T700, T700S, T800, T800H, T1000, T1000G or T1100G; the resin material is selected from at least one of low-temperature resistant epoxy resin, modified epoxy resin, cyanate ester resin or bismaleimide resin. The non-vacuum closed-cell foam layer is selected from at least one of polyurethane foam, polyisocyanurate foam, polymethacrylamide foam, phenolic foam, polyvinyl chloride foam, polyetherimide foam, aerogel-reinforced foam, or hollow microsphere-reinforced foam. The composite material shell is made of fiber-reinforced resin-based composite material, which is selected from at least one of carbon fiber-reinforced epoxy resin-based composite material, glass fiber-reinforced epoxy resin-based composite material, and aramid fiber-reinforced resin-based composite material.
10. A method for manufacturing a hydrogen storage container according to any one of claims 1-9, characterized in that, The manufacturing method includes: Provide a metal lining structure; Fibers are wound around the outer surface of the metal liner structure to form a composite material bearing layer, and then a first curing treatment is performed. A non-vacuum closed-cell foam layer is formed on the outside of the cured composite material pressure-bearing layer; Fibers are wound around the outer surface of the non-vacuum closed-cell foam layer to form a composite material shell, and a second curing process is performed to make the composite material shell, the non-vacuum closed-cell foam layer and the composite material pressure-bearing layer form an integrated sandwich structure.
11. The manufacturing method according to claim 10, characterized in that, Both the first curing process and the second curing process employ multi-stage temperature-increasing curing. The multi-stage temperature-curing process includes: First stage: Incubate at 353-363K for 0.5-1 hour; Second stage: Heat to 383-393K and hold for 2-3 hours; Third stage: Heat to 403-413K and hold for 2-3 hours; The heating rate of both the first curing process and the second curing process is controlled at 274-276 K / min between each stage.
Citation Information
Patent Citations
Carbon fiber reinforced foam core sandwich plate composite structure and preparation method thereof
CN121200507A
Plastic foam integral molding composite panel and its manufacture
JP1999300865A
Light-weight cryogenic-compatible pressure vessel
JP2023167249A
Method for manufacturing compositely molded 99-mpa-grade hydrogen storage container for hydrogen refueling station
WO2024041262A1